ANALISIS GAYA BELAJAR PESERTA DIDIK BERPRESTASI PADA MATA PELAJARAN BIOLOGI DI KELAS XI SMA NEGERI 3 MANADO - Takasihaeng, Grace Merryrose; Rayer, Debby J. J.; Posumah, Dany Ch (SOSCIED, 2025)
This research is motivated by the occurrence of various difficulties in the learning process, namely teachers have not used a variety of learning methods according to students' learning styles so that students' interest in learning is still lacking. This research is a qualitative descriptive study. Data collection techniques using questionnaires, interviews and documentation. The data sources in the study were outstanding biology students in class XI. The sources in the study were 3 outstanding students who obtained the highest scores in Biology subjects in Class XI A-XI G of SMA Negeri 3 Manado. Based on the data obtained through research and data validity tests using data triangulation, it can be concluded from the results of the study which show that outstanding students in Biology subjects in Class XI A-XI G of SMA Negeri 3 Manado have a combined learning style of visual, auditory and kinesthetic (VAK). However, among these learning styles, the most dominant is the kinesthetic learning style, from 21 students it was found that 3 students had a tendency towards a visual learning style, 5 students had a tendency towards an auditory learning style, 10 students had a tendency towards a kinesthetic learning style and 3 students had a combination of learning styles, namely: 1 student had a visual kinesthetic learning style, 1 student had an auditory kinesthetic learning style, and 1 student had a visual, auditory and kinesthetic learning style.